Parking Retribution Management at the Transportation Service of Sidoarjo Regency - Fardana, Miftachul; Indartuti, Endang; Rochim, Achluddin Ibnu (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
This study aims to analyze the management of parking fees by the Sidoarjo Regency Transportation Agency and identify inhibiting factors and optimization efforts. Using descriptive qualitative methods, this study examines the implementation of management functions, including planning, organizing, implementing, and controlling (POAC). The results indicate that the planning aspect faces data validity constraints, resulting in unrealistic revenue targets. Organization is hampered by contractual disputes with third parties, which weakens field coordination. Field implementation is still characterized by manual practices that are prone to leaks, while supervision has not been effective in suppressing illegal parking. The main inhibiting factors include limited Human Resources (HR), public rejection of the payment culture, and a non-integrated system. Efforts undertaken include digital transformation (e-parking) and joint operations. This study recommends accelerating digitalization and improving databases to increase Regional Revenue (PAD).